EFEKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BATANG POHON JAMBU MEDE (ANACARDIUM OCCIDENTALE L) PADA BAKTERI SHIGELLA DYSENTERIAE - Hayatus Sa’adah; Nor Latifah; Jihan Jihan (Jurnal Inovasi Penelitian, 2022)
Dysentery is a digestive disorder that has symptoms of bowel movements with a watery consistency, mucus and blood with a frequency of bowel movements 3 times/day. Dysentery can be caused by the bacterium Shigella dysenteriae and natural treatment can be done using medicinal plants that have antibacterial effectiveness, one of which is the bark of the cashew tree. The bark of the cashew tree trunk (Anacardium occidentale L) contains secondary compounds belonging to the tannin class which have antibacterial properties. The purpose of this study was to determine the antibacterial effectiveness of the ethanol extract from the bark of the cashew tree trunk on S. dysenteriae bacteria. The antibacterial effectiveness test method in this study used the disc diffusion method. The concentration of extracts made was 5%, 10%, 15% and 20%. The results showed that the bacterial inhibition zone formed was marked by a clear zone around the paper disc and the area of ​​the clear zone was measured using a ruler. Concentration of ethanol extract of cashew tree bark 5% did not show antibacterial effectiveness on S. dysenteriae, while concentrations of cashew tree bark 10%, 15% and 20% had antibacterial effectiveness on S. dysenteriae because it had inhibitory power with clear zone diameter. 8mm, 9mm and 10mm respectively.